Photochemistry and Photobiology of the Spore Photoproduct: A Fifty Year Journey - Setlow, Peter (Photochem Photobiol, 2015)
Fifty years ago, a new thymine dimer was discovered as the dominant DNA photolesion in UV irradiated bacterial spores [Donnellan, J. & Setlow R. (1965) Science, 149, 308–310], which was later named the spore photoproduct (SP). Formation of SP is due to the unique environment in the spore core that features low hydration levels favoring an A-DNA conformation, high levels of calcium dipicolinate that acts as a photosensitizer, and DNA saturation with small, acid-soluble proteins that alters DNA structure and reduces side reactions. In vitro studies reveal that any of these factors alone can promote SP formation; however, SP formation is usually accompanied by the production of other DNA photolesions. Therefore, the nearly exclusive SP formation in spores is due to the combined effects of these three factors. SP photoreaction is proved to occur via a unique H-atom transfer mechanism between the two involved thymine residues. Successful incorporation of SP into an oligonucleotide has been achieved via organic synthesis, which enables structural studies that reveal minor conformational changes in the SP-containing DNA. Here, we review the progress on SP photochemistry and photobiology in the past fifty years, which indicates a very rich SP photobiology that may exist beyond endospores.